Heat-Shock Protein 27 kinetics in end stage renal disease patients - I Griveas (Archives of Clinical Nephrology - Peertechz Publications, 2020)
Atherosclerosis is one of the most significant yet unresolved problems in patients on regular Hemodialysis (HD) with major impact on morbidity and mortality of patients with end-stage renal disease (ESRD). There is growing evidence that atherosclerosis may-at least in part- result from autoimmune processes, in which the family of Heat-Shock Proteins (HSP) may be involved [1].